2015
DOI: 10.1038/nn.4193
|View full text |Cite
|
Sign up to set email alerts
|

Oligodendrocyte death results in immune-mediated CNS demyelination

Abstract: Although multiple sclerosis is a common neurological disorder, the origin of the autoimmune response against myelin, which is the characteristic feature of the disease, remains unclear. To investigate whether oligodendrocyte death could cause this autoimmune response, we examined the oligodendrocyte ablation Plp1-CreERT;ROSA26-eGFP-DTA (DTA) mouse model. Approximately 30 weeks after recovering from oligodendrocyte loss and demyelination, DTA mice develop a fatal secondary disease characterized by extensive mye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
144
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(154 citation statements)
references
References 46 publications
7
144
0
3
Order By: Relevance
“…In both rodent and primate models of multiple sclerosis, for example, brain antigens were increased in the cervical lymph nodes (80,81). After stroke, brain injury, or oligodendrocyte death induced by diphtheria toxin, myelin antigens have similarly been found to accumulate in the cervical lymph nodes (82)(83)(84). Drainage of brain antigens has been observed in animal models not only of autoimmune diseases but also of Alzheimer's disease.…”
Section: R E V I E W S E R I E S : G L I a A N D N E U R O D E G E N mentioning
confidence: 99%
See 1 more Smart Citation
“…In both rodent and primate models of multiple sclerosis, for example, brain antigens were increased in the cervical lymph nodes (80,81). After stroke, brain injury, or oligodendrocyte death induced by diphtheria toxin, myelin antigens have similarly been found to accumulate in the cervical lymph nodes (82)(83)(84). Drainage of brain antigens has been observed in animal models not only of autoimmune diseases but also of Alzheimer's disease.…”
Section: R E V I E W S E R I E S : G L I a A N D N E U R O D E G E N mentioning
confidence: 99%
“…It was recently demonstrated that induction of massive death of oligodendrocytes leads to the generation of autoreactive T cells that can indeed induce multiple sclerosis-like symptoms in mice (83). Furthermore, expression of a foreign antigen on oligodendrocytes induces T cell response in the draining lymph nodes (97).…”
Section: Generation Of Immune Responses and Immune Privilegementioning
confidence: 99%
“…Adoptive transplantation of these T cells into naïve hosts was sufficient to transfer disease. It is likely that the initial insult served to prime the immune system, which eventually led to an autoimmune response and subsequent CNS demyelination [69].…”
Section: Cell Death Models Of Demyelinationmentioning
confidence: 99%
“…The outside-in hypothesis suggests that the immune system is initially triggered and becomes primed to infiltrate into the CNS to attack myelin sheaths (McFarland & Martin, 2007;Stys et al, 2012). In contrast, the inside-out hypothesis suggests that the initial, or primary, insult is cytodegeneration of the oligodendrocyte and myelin that subsequently triggers an immune response (Barnett & Prineas, 2004;Henderson et al, 2009;Stys et al, 2012;Traka et al, 2015). The heterogeneity of patient lesions, classified as Pattern I -Pattern IV, further supports the difficulties in identifying the etiology, as Patterns I and II demonstrate T-cell inflammatory mediated demyelination and Patterns III and IV suggest oligodendrocyte and myelin cytodegeneration (Denic et al, 2011).…”
Section: Introductionmentioning
confidence: 99%